Enabling Communication Technologies for Smart Cities - Yaqoob, Ibrar; Hashem, Ibrahim Abaker Targio; Mehmood, Yasir; Gani, Abdullah; Mokhtar, Salimah; Guizani, Sghaier (Institute of Electrical and Electronics Engineers, 2017)
Tremendous advancements in heterogeneous communication technologies have enabled smart cities objects to interact with each other while ensuring network connectivity. However, these communication technologies cannot provide flawless connectivity in smart cities due to the coexistence of thousands of devices, which brings about several problems. In this article, we discuss the enabling communication and networking technologies used in smart cities. The similarities and differences among different communication technologies based on the important parameters are also analyzed. Moreover, a taxonomy is devised by classifying the literature based on future and emerging technologies, modern communication technologies, IEEE wireless technology standards, objectives, network classes, and mode of operations. Furthermore, some reported case studies of different cities (Barcelona, Stratford, Singapore, and Porto) are also presented. Lastly, several research challenges, such as interference management, scalable wireless solutions, interoperability support among heterogeneous wireless networks, mobility management, and high energy consumption that remain to be addressed for enabling unimpaired connectivity in smart cities are discussed as future research directions.